TEACHING SCHOOL ALGEBRA LESSONS USING COMPUTER ALGEBRA SYSTEMS (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This article analyzes the pedagogical opportunities of using Computer Algebra Systems (CAS) in teaching algebra in general secondary schools. The use of CAS tools in solving algebraic problems, studying functions, and mathematical modeling processes is discussed as a means of developing students’ mathematical competencies. In addition, the methodological aspects of integrating computer algebra systems into the school algebra curriculum and the advantages of this approach are examined.
Keywords: algebra, computer algebra systems, CAS, mathematics education, GeoGebra, Maple, Mathematica, mathematical competence, information technologies.